2006
DOI: 10.3844/jcssp.2006.595.599
|View full text |Cite
|
Sign up to set email alerts
|

Single Stuck-At Fault Diagnosing Circuit of Reed-Muller Canonical Exclusive-Or Sum of Product Boolean Expressions

Abstract: Abstract:A testable design with a universal test set for single stuck-at zero and stuck-at one faults of Reed-Muller canonical form of Exclusive-OR sum of product logic expressions is proposed. The test circuit detects almost all the single stuck-at faults and needs only simple modifications for variations in the circuit under test. The number of test vectors is also quite small compared with the classical method. The factor of un-identifiability is discussed and a new quantification parameter for the fault di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Zhongliang (2002) demonstrated that the single stuck-at fault detection can be achieved with only n+5 test vectors. Two methods, each with a small modification in this scheme in ESOP RMC circuits had been proposed by Neelakantan and Jeyakumar (2006a) for analysis and diagnosis of single stuck-at faults. This study is an extension of the work done by Neelakantan and Jeyakumar (2006b) for the analysis and diagnosis of OR-bridging faults in any of the pairs of data and control lines of the ESOP RMC circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Zhongliang (2002) demonstrated that the single stuck-at fault detection can be achieved with only n+5 test vectors. Two methods, each with a small modification in this scheme in ESOP RMC circuits had been proposed by Neelakantan and Jeyakumar (2006a) for analysis and diagnosis of single stuck-at faults. This study is an extension of the work done by Neelakantan and Jeyakumar (2006b) for the analysis and diagnosis of OR-bridging faults in any of the pairs of data and control lines of the ESOP RMC circuits.…”
Section: Introductionmentioning
confidence: 99%